A personal perspective on clinical research in Enteric Fever. - Farrar, J (2007)
With the global spread of enteric fever, the emergence of Salmonella enterica serovar Paratyphi as a major pathogen (particularly in Asia), the spread of drug resistance, and the global increase in the incidence of non-Typhi salmonella, particularly in patients coinfected with human immunodeficiency virus, there is now more than ever a need for clinical research in enteric fever. The work of Ted Woodward 60 years ago remains relevant today, and his holistic approach to clinical research inspired many of us to follow in his footsteps. There remains healthy discussion among clinicians about the best treatment for enteric fever, and pragmatic, well-designed, randomized controlled trials are required to provide clear evidence. Vaccines and public health measures will have the greatest impact on the overall burden of disease; however, while we wait for these measures, prompt diagnosis and early treatment with the best available and affordable drug will help patients, reduce transmission within the community, and potentially help to contain the spread of drug resistance. Better integration of clinical medicine with epidemiology, public health, vaccine development, and modern laboratory science will help to yield tangible benefits for the vast number of people who have this disease.